Topological Defects in Metal‐Free Nanocarbon for Oxygen Electrocatalysis. Issue 32 (11th May 2016) - Tang, Cheng; Wang, Hao‐Fan; Chen, Xiang; Li, Bo‐Quan; Hou, Ting‐Zheng; Zhang, Bingsen; Zhang, Qiang; Titirici, Maria‐Magdalena; Wei, Fei
Abstract : A bifunctional graphene catalyst with abundant topological defects is achieved via the carbonization of natural gelatinized sticky rice to probe the underlying oxygen electrocatalytic mechanism. A nitrogen‐free configuration with adjacent pentagon and heptagon carbon rings is revealed to exhibit the lowest overpotential for both oxygen reduction and evolution catalysis. The versatile synthetic strategy and novel insights on the activity origin facilitate the development of advanced metal‐free carbocatalysts for a wide range of electrocatalytic applications.